Destino Ocupacional dos Egressos do Curso de Licenciatura em Pedagogia da Unesp/Rio Claro no período 1993-1997 - Arilda Schmidt Godoy; Lígia Scalzitti (Universidade Estadual Paulista Júlio de Mesquita Filho, 2007)
This study identifies the professional paths of the alumni of the pedagogy undergraduate program from UNESP in Rio Claro, São Paulo State. The main objetive was to assess the extent to which they were able to get jobs really pertaining to their professional field of work. The study also evaluates the importance and the contribution of the program to the alumni efficiency at work, according to their own view.